"With recruitment I always feel I need to listen to my gut": the role of intuition in employee selection. Issue 4 (27th May 2014) - Miles, Andrew; Sadler-Smith, Eugene
Abstract : Purpose: – This qualitative study of managers' use of intuition in the selection process aimed to understand if and how managers use intuition in employee hiring decisions and suggest ways in which the use of intuition might be improved. The paper aims to discuss these issues. Design/methodology/approach: – Semi-structured, in-depth interviews were conducted with managers from a range of backgrounds, and with varying experience of recruitment and selection. Findings: – Findings revealed that reasons for the use of intuition included personal preferences, resource constraints and recognition of the limitations of more structured approaches. Intuition was used an indicator for performance, personality and person-environment fit. Intuition tended to be used with requisite caution; participants were aware of its limits, the potential for bias and the difficulties in justifying its use; several participants used their intuitions in concert with more structured, non-intuition based approaches. Research limitations/implications: – The small-scale investigative study has limited generalisability. The paper concludes with five specific recommendations on how to improve managers' understanding and use of intuition in employee selection. Originality/value: – Despite increased interest in intuition in management there is a paucity of qualitative studies of intuition-in-use in management in general and in personnel in particular. This research helps to fill this gap.